2015
DOI: 10.1097/shk.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prehospital Blood Products to Attenuate Acute Coagulopathy of Trauma in a Model of Severe Injury and Shock in Anesthetized Pigs

Abstract: Acute trauma coagulopathy (ATC) is seen in 30% to 40% of severely injured casualties. Early use of blood products attenuates ATC, but the timing for optimal effect is unknown. Emergent clinical practice has started prehospital deployment of blood products (combined packed red blood cells and fresh frozen plasma [PRBCs:FFP], and alternatively PRBCs alone), but this is associated with significant logistical burden and some clinical risk. It is therefore imperative to establish whether prehospital use of blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
1
37
0
1
Order By: Relevance
“…This is an opportunistic prospective observational study that investigates the haemodynamic and microcirculatory variables for some of the subjects of a previously published porcine experimental study. The original experimental study was undertaken to address the effects of different initial resuscitation fluids on the development of trauma-induced coagulopathy, the results of which have been published elsewhere [ 10 ]. Data were obtained from experiments conducted with the presence of an investigator trained in the acquisition of microcirculatory images.…”
Section: Methodsmentioning
confidence: 99%
“…This is an opportunistic prospective observational study that investigates the haemodynamic and microcirculatory variables for some of the subjects of a previously published porcine experimental study. The original experimental study was undertaken to address the effects of different initial resuscitation fluids on the development of trauma-induced coagulopathy, the results of which have been published elsewhere [ 10 ]. Data were obtained from experiments conducted with the presence of an investigator trained in the acquisition of microcirculatory images.…”
Section: Methodsmentioning
confidence: 99%
“…In 2005, Chhabra and co‐workers showed that the N‐terminal fragment of gelsolin could bind to and disrupt actin–DNase complexes, in turn restoring enzymatic activity. FFP is not only effective in treating trauma but was shown previously to attenuate extracellular nucleosome levels and depletion of DNase, and to provide neuroprotection in models of traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Damage control resuscitation is a strategy of delivering blood as initial therapy and may be the preferred fluid infused in future conflicts. While there is an associated risk of developing metabolic derangements and coagulopathy with crystalloid resuscitation, the survival benefit outweighs this risk in critically injured patients and can be a lifesaving intervention [1720]. Crystalloid (isotonic solutions) is the fluid of choice for the treatment of acute hypovolemic shock according to the Advanced Trauma Life Support (ATLS) book [21].…”
Section: Discussionmentioning
confidence: 99%